Pengembangan Usaha Jual Beli Karet dari Perspektif Studi Kelayakan Bisnis di Desa Rantau Sialang - Ellisyah Mindari (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2022)
The Law on Villages' objectives can be realized more quickly through the independent and cooperative development of a village's economic potential. In emerging villages, maximizing local economic potential is a response to strategic analysis. If we hope that the business we start or run does not suffer significant losses, investment decisions must be made. Villagers of Rantau Sialang, who work primarily as rubber farmers, will be provided with information and comprehension of the perspective on business feasibility studies in order to provide them with the tools they need to create business feasibility studies for managing their enterprises. Head of LPPM STIE Rahmaniyah Sekayu and Head of Rantau Sialang Village's are partners in this project. The service approach takes the form of lectures (written modules, slide shows, and video playback with projector material), discussions, and hands-on experience for creating company feasibility studies and assessing business activity plans. The participation of participants, the fact that the final evaluation value was greater than the first evaluation value, the excitement with which the material was received, and the occurrence of cordial conversation during discussions all contributed to the success of this activity.